Engagement and Short-term Abstinence Outcomes Among Blacks and Whites in the National Cancer Institute's SmokefreeTXT Program. Issue 9 (19th September 2019) - Robinson, Cendrine D; Wiseman, Kara P; Webb Hooper, Monica; El-Toukhy, Sherine; Grenen, Emily; Vercammen, Laura; Prutzman, Yvonne M
Abstract: Introduction: Text-messaging programs for smoking cessation improve abstinence outcomes in the general population. However, little is known about engagement and abstinence outcomes among African Americans in text-messaging smoking cessation programs. The current study compares engagement and abstinence between Blacks and Whites in the National Cancer Institute's SmokefreeTXT program. Method: Data were from Blacks ( n = 1333) and Whites ( n = 7154) who enrolled in the 6-week SmokefreeTXT program between August 2017 and June 2018. We assessed the association between race and program initiation and completion; responses to weekly smoking cessation, mood, and craving assessments; and self-reported abstinence using multivariable logistic regression. Results: Blacks and Whites initiated the program at a similar frequency, yet Blacks were more likely to complete the program (adjusted odds ratio [AOR] = 1.71, 95% confidence interval [CI] = 1.43 to 2.06). Blacks were less likely to respond to all seven abstinence, mood, and craving assessments (eg, AOR of quit day responses = 0.63, 95% CI = 0.51 to 0.77; 6-week AOR = 0.50, 95% CI = 0.34 to 0.72). Self-reported abstinence was lower among Blacks for all seven smoking assessments (eg, quit day abstinence AOR = 0.52, 95% CI = 0.41 to 0.68; 6-week abstinence AOR = 0.58, 95% CI = 0.38 to 0.89). Conclusion: Although Blacks were more likely than Whites to complete the SmokefreeTXT program, they were less likely to engage with the program by responding to assessment questions and had lower abstinence rates. Qualitative research may reveal unique barriers to engagement among Blacks. Implications: Black smokers enrolled in a nationwide mobile smoking cessation program at a rate comparable to White smokers. However, they were significantly less likely to engage with the program or quit smoking. This study highlights the need to examine barriers to cessation for Black smokers.